Professores de Matemática dos anos finais do ensino fundamental em início de carreira: desafios, vivências e sentimentos - Seriani, Raquel (2015)
This qualitative research aims to identify challenges, experiences and feelings of mathematics teachers beginning their careers and who teach in the final years of elementary school. Data were collected through semi structured interviews with five teachers from a public school in São Paulo. The existing problems in the professional life of the beginner teacher and the failure of papers about the practice in first step career teachers encouraged the development of this research. To broaden the discussion on how beginner teachers face challenges and difficulties, it was sought to support in researchers who study the early stages of the teaching career. Huberman (1995) encouraged this study in relation to the life cycle of the teachers and the identification of phases which define the variables and their professional development. Lima (2006) contributed with the presentation of his own characteristics of his first career, where major brands of identity and professional attitude occur. Marcelo Garcia (1999) brought elements that contribute to the integration into the teaching profession concerning the baseline as the tensions and learning in unfamiliar contexts and the acquisition of professional knowledge and the achieving of personal balance. The results indicated that the beginner teachers face related difficulties, most of the time, indiscipline, student motivation and lack of support from directors and workmates. They also indicated that beginner teachers have feelings of loneliness due to the lack of collective work, inexperience and insecurity. It was observed that the difficulties in relation to the teaching of mathematics came from the training course in undergraduate programs, notably as regards the lack of coordination between specific and pedagogical disciplines. The data have revealed that the professional initiation period is a great importance to the difficulties and challenges today and they have indicated that more and more integration programs should be a matter of concern of directors and teachers of public politics